2013
DOI: 10.1371/journal.pone.0082176
|View full text |Cite
|
Sign up to set email alerts
|

A Leaderless Genome Identified during Persistent Bovine Coronavirus Infection Is Associated with Attenuation of Gene Expression

Abstract: The establishment of persistent viral infection is often associated with the selection of one or more mutant viruses. For example, it has been found that an intraleader open reading frame (ORF) in genomic and subgenomic mRNA (sgmRNA) molecules is selected during bovine coronavirus (BCoV) persistence which leads to translation attenuation of the downstream ORF. Here, we report the unexpected identification of leaderless genomes, in addition to leader-containing genomes, in a cell culture persistently infected w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 69 publications
1
16
0
Order By: Relevance
“…Several studies have suggested that cis-acting RNA elements located at the 5 0 -terminus of the genome are also critical for (À)-strand RNA synthesis [8,10,49,50]. In the current study, we found that in addition to the 3 0 -terminal sequence or structure, the binding affinity of N protein to the 5 0 -terminal sequence also correlates with (À)-strand RNA synthesis.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Several studies have suggested that cis-acting RNA elements located at the 5 0 -terminus of the genome are also critical for (À)-strand RNA synthesis [8,10,49,50]. In the current study, we found that in addition to the 3 0 -terminal sequence or structure, the binding affinity of N protein to the 5 0 -terminal sequence also correlates with (À)-strand RNA synthesis.…”
Section: Discussionsupporting
confidence: 57%
“…RNA was then collected at 8 h posttransfection (hpt) and subjected to RT-qPCR to evaluate the effect of poly(A) tail length on (À)-strand synthesis efficiency. It should be noted that there is no possibility of DI RNA-BCoV genome recombinant synthesized at 8 hpt because no RT-PCR product was observed (data not shown) using previously described methods [8,16,39]. Surprisingly, (À)-strand RNA synthesis was still detected using DI RNA with no poly(A) tail (BM0A, Fig.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Infective BRSV has been isolated from lymph nodes 71 days post infection (74). BCoV persistence has been demonstrated in cell culture (75). Long-term PCR positivity in calves has been shown in one experimental study, but transmission potential was not confirmed by virus isolation/sentinel trials nor was sequencing of virus done to exclude new infection (76).…”
Section: How Can the Viruses Be Eliminated From Infected Herds?mentioning
confidence: 99%
“…However, variations at the 5′ terminal sequence in mouse hepatitis virus-A59 (MHV-A59), a mouse coronavirus, have not been identified, but instead a mutation at nucleotide (nt) 77 in the genome leads to the synthesis of the start codon AUG and subsequent translation enhancement [ 18 ]. The recently identified leaderless genome in BCoV has also been suggested to be associated with an attenuation of translation during BCoV persistence [ 24 ]. These studies focus only on the structural changes at the 5′ end of the genome and subgenome during persistence [ 18 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%